THE EFFECTIVENESS OF ENGLISH CLUB DISCUSSION TO IMPROVE STUDENTS’ SPEAKING ABILITY AT TENTH GRADE OF THE MA PUTRA ISHLAHUDDINY IN ACADEMIC YEAR 2023/2024 - sofyan assauri (Journal of English Education and Literature, 2024)
The purpose of this research was to find out the effect of applying English Club Discussion to improve students’ speaking ability at Tenth Grade of the MA Putra Ishlahuddiny. This study used a pre-experimental design with a one-group pre-test and post-test design. The researcher employed pre-experimental methods, in which the experimental class was carried out by using English Club Discussion, in which the teacher presented the material in front of the class and students looked at and paid attention to him. And after that they will be divided into several discussion groups to discuss the material that the teacher has conveyed. The researcher used this method to know the Effectiveness of English Club in improving students’ speaking ability. The comparison between the pre-test and post-test score depends on the success of the treatment. The findings showed the English club discussion had significant effects on students' speaking abilities. This can be observed in the students' pre-test average score (40), which improved to (60) in the post-test, representing a 59% improvement. According to the t-test analysis, Sig (2-tailed) is 0.000, which is less than = 0.05 (0.0000.05). The Alternative Hypothesis (Ha) was accepted while the Null Hypothesis (Ho) was rejected. Based on the results, it is possible to conclude that the English Club Discussion was effective in increasing the students' speaking Ability at the tenth grade of MA Putra Ishlahuddiny Kediri.The purpose of this research was to find out the effect of applying English Club Discussion to improve students’ speaking ability at Tenth Grade of the MA Putra Ishlahuddiny. This study used a pre-experimental design with a one-group pre-test and post-test design. The researcher employed pre-experimental methods, in which the experimental class was carried out by using English Club Discussion, in which the teacher presented the material in front of the class and students looked at and paid attention to him. And after that they will be divided into several discussion groups to discuss the material that the teacher has conveyed. The researcher used this method to know the Effectiveness of English Club in improving students’ speaking ability. The comparison between the pre-test and post-test score depends on the success of the treatment. The findings showed the English club discussion had significant effects on students' speaking abilities. This can be observed in the students' pre-test average score (40), which improved to (60) in the post-test, representing a 59% improvement. According to the t-test analysis, Sig (2-tailed) is 0.000, which is less than = 0.05 (0.0000.05). The Alternative Hypothesis (Ha) was accepted while the Null Hypothesis (Ho) was rejected. Based on the results, it is possible to conclude that the English Club Discussion was effective in increasing the students' speaking Ability at the tenth grade of MA Putra Ishlahuddiny Kediri.